First Killed Moose - sp001Angalin (Andrey Filchenko, 2007)
Language_Name: Vasyugan and Alexandrovo Khanty dialects Language_Region: Asia Language_Country: Russian Federation Project_Status: Complete Year: 2007 Start_Date: 2007-07-01 End_Date: 2008-02-28